Spatial distribution of lactating sows in thermally controlled facilities and their productive performance during the pre-weaning phase - Flávio de Aguiar Coelho; Viviane Maria Oliveira dos Santos; Larissa Venier de Oliveira; Débora Minetti Sarturi; Fernanda Mariane dos Santos; Erick Marlon Pereira; Ariadne Maria Portilho Saturnino da Silva; Rodrigo Gonçalves Mateus (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to evaluate the effect of a farrowing unit with an adiabatic evaporative cooling system with negative pressure and longitudinal air flow on the catabolism and performance of lactating sows. Twenty eight multiparous sows were housed in a farrowing unit with cooling system. During the 24 days of lactation, the animals were submitted to two treatments: pad cooling, with sows close to the evaporative system, and exhaust, with sows close to the exhaust fans. The microclimatic variables temperature and humidity, as well as intake, body condition score, and litter weight, which indicate the productive performance of the sows, were assessed. The variables were subjected to mean analysis using the generalized linear model (GLM). An installation equipped with a negative pressure adiabatic evaporative system does not provide homogeneous microclimate throughout the facility, resulting in different thermal environments for the lactating sows. Placing sows near evaporative pads does not affect body condition scores and improves piglet weight and sow feed intake in the farrowing pen.